Reactivity of alveolar macrophages in lung cancer patients and healthy subjects: surface ICAM-1 after INF-gamma stimulation in vitro - Hoser, G; Grubek-Jaworska, H; Droszcz, P; Domagała-Kulawik, J; Dabrowska, M; Chazan, R (Folia histochemica et cytobiologica, 2002)
The linearity of ICAM- I expression on alveolar macrophages (AM) before and after INF-gamma stimulation in healthy and lung cancer subjects were compared. AM were collected by bronchoalveolar lavage and incubated with/without INF-gamma according to standard procedures. The harvested cells were analyzed by flow cytometry using monoclonal antibodies against leucocytes and macrophages. Only viable cells were analyzed. Stimulation with INF-gamma revealed two AM subpopulations of similar size differentiated in the intensity of ICAM-1 expression. They were not distinctly marked in every studied case. Our preliminary results did not confirm the previously reported decreasing reactivity of AMs after INF-gamma stimulation in lung cancer patients.